Health and social support services in older adults recently discharged from hospital: service utilisation and costs and exploration of the impact of a home-exercise intervention. Issue 1 (December 2016) - Farag, I.; Howard, K.; O'Rourke, S.; Ferreira, M.; Lord, S.; Close, J.; Vogler, C.; Dean, C.; Cumming, R.; Sherrington, C.
Abstract Background Admission to hospital can lead to persistent deterioration in physical functioning, particularly for the more vulnerable older population. As a result of this physical deterioration, older people who have been recently discharged from hospital may be particularly high users of health and social support services. Quantify usage and costs of services in older adults after hospitalisation and explore the impact of a home-exercise intervention on service usage. Method The present study was a secondary analysis of data from a randomised controlled trial (ACTRN12607000563460). The trial involved 340 participants aged 60 years and over with recent hospitalisation. Service use and costs were compared between intervention (12 months of home-exercise prescribed in 10 visits from a physiotherapist) and control groups. Results 33 % of participants were re-admitted to hospital, 100 % consulted a General Medical Practitioner and 63 % used social services. 56 % of costs were associated with hospital admission and 22 % with social services. There was reduction in General Medical Practitioner services provided in the home in the intervention group (IRR 0.23, CI 0.1 to 0.545, p < 0.01) but no significant between-group difference in service use or in costs for other service categories. Conclusion There appears to be substantial hospital and social service use and costs in this population of older people. No significant impact of a home-based exercise program was evident on service use or costs. Trial registration Australian and New Zealand Clinical Trial RegistryACTRN12607000563460 >TrialSearch.